Alternative bankruptcy prediction models using option-pricing theory - Charitou, Andreas; Dionysiou, Dionysia; Lambertides, Neophytos; Trigeorgis, Lenos (My University, 2013)
We examine the empirical properties of the theoretical Black-Scholes-Merton (BSM) bankruptcy model. We evaluate the predictive ability of various existing modifications of the BSM model and extend prior studies by estimating volatility directly from market-observable returns on firm value. We show that parsimonious models using our direct market-observable volatility estimate perform better than alternative, more sophisticated, models. Our findings suggest the adoption of simpler modelling approaches relying on market data when implementing the BSM model.
Keywords: Bankruptcy prediction; Option-pricing theory; Volatility estimation